2021
DOI: 10.1021/acsami.1c01869
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell-Mediated Gene Delivery for In Situ Accelerated Endothelialization of a Vascular Graft

Abstract: As an urgently needed device for vascular diseases, the small-diameter vascular graft is limited by high thrombogenicity in clinical applications. Rapid endothelialization is a promising approach to construct an antithrombogenic inner surface of the vascular graft. The main bottleneck for rapid endothelialization is the adhesion, migration, and proliferation of endothelial cells (ECs) in situ of the small-diameter vascular graft. Herein, we innovatively fabricated an intelligent gene delivery small-caliber vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…The degradation of PTMC can be accelerated in the presence of enzymes. The same phenomenon was reported in previous articles for non‐cross‐linked PTMC 7 . Meanwhile, according to our previous study, the mass loss of non‐cross‐linked PTMC in enzyme solution was 5.3% ± 0.4%.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The degradation of PTMC can be accelerated in the presence of enzymes. The same phenomenon was reported in previous articles for non‐cross‐linked PTMC 7 . Meanwhile, according to our previous study, the mass loss of non‐cross‐linked PTMC in enzyme solution was 5.3% ± 0.4%.…”
Section: Resultssupporting
confidence: 89%
“…Compared with metal materials and nondegradable polymer materials, biodegradable polymers have the advantage of not requiring secondary surgery 3 . In recent decades, polylactic acid, 4 polycaprolactone, 5 polyglycolic acid, 6 and other absorbable polymer materials are increasingly favored by researchers 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…(B) REDV peptide and MMP cleavable peptide comodified surface to programmatically attract VECs and release ZNF580 gene complexes. 209 Copyright 2021, American Chemical Society.…”
Section: Chemical Modificationmentioning
confidence: 99%
“…5B). 209 The comodified surface could selectively adhere ECs firstly, and subsequently release gene nanocomplexes to transfect ECs, which synergistically accelerates re-endothelialization. Recently, Cheng's group constructed smart exosome-eluting scaffolds by using ROS responsive groups to link metal scaffolds to phosphatidylethanolamine-polyethylene glycol (DSPE-PEG) and then attaching exosomes uniformly to metal scaffolds.…”
Section: Chemical Modificationmentioning
confidence: 99%
“…NAv/biotin complex is the strongest non-covalent interaction known in nature (Kd = 10 -14 mol/L) and has been used in a wide variety of applications including: bioassays, [43] drug delivery [44] and tissue engineering. [45] As such, neutravidin (and the streptavidin companion) are used in immunosensing applications because of their reduced nonspecific binding. [46] It has been demonstrated that passive surface adsorption of Neutravidin leads to protein alteration in terms of conformation and aggregation (multilayers) which may alter the interface outcome, and that can be overcome by the use of PEG tethers.…”
Section: Introductionmentioning
confidence: 99%